Experimental studies of ion emission from RPI-IBIS facility and modeling of ion motions - Malinowski, K.; Czaus, K.; Sadowski, M.J.; Skladnik-Sadowska, E.; Garkusha, I.E.; Tereshin, V.I. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
The paper presents the recent measurements of ion beams emitted from an RPI-IBIS plasma injector and some preliminary results of the theoretical modeling. The RPI-IBIS facility was equipped with coaxial electrodes made of thin molybdenum rods and a fast acting electromagnetic valve for the injection of a working gas. Plasma discharges were initiated with a variable time delay (τ ) after the gas injection and they were powered from a condenser bank charged to 30 kV, 30 kJ. The first part describes measurements of spatial distributions and energies of intense ion beams, which were performed by means of ion-pinhole cameras equipped with nuclear track detectors. Detailed analysis of ion mass- and energy-spectra was performed by means of a Thomson analyzer. The second part presents numerical simulations of ion motions in the RPI-IBIS facility, which were performed on the basis of a single-particle model. Представлены результаты исследований ионных пучков, эмитируемых стержневым инжектором RPI-IBIS, и некоторые предварительные результаты теоретического моделирования. RPI-IBIS оснащен коаксиальными электродами в виде тонких молибденовых стержней и быстодействующим электромагнитным клапаном для инжекции рабочего газа. Разряд инициировался с варьируемым временем задержки по отношению к напуску газа при напряжении на конденсаторной батарее 30 кВ. В первой части описаны измерения пространственных распределений и энергий интенсивных ионных пучков. Детальный анализ массовых и энергетических спектров проведен с использованием анализатора Томпсона. Вторая часть посвящена численному моделированию движения ионов в RPI-IBIS, которое проведено на основе одночастичной модели. Представлено результати досліджень іонних пучків, емітуємих стрижневим інжектором RPI-IBIS, і деякі попередні результати теоретичного моделювання. RPI-IBIS оснащений коаксіальними електродами у виді тонких молібденових стрижнів і швидко діючим електромагнітним клапаном для інжекції робочого газу. Розряд ініціювався з варіацією часу затримки стосовно напуску газу при напрузі на конденсаторній батареї 30 кВ. У першій частині описано виміри просторових розподілів і енергій інтенсивних іонних пучків. Детальний аналіз масових і енергетичних спектрів проведено з використанням аналізатора Томпсона. Друга частина присвячена чисельному моделюванню руху іонів у RPI-IBIS, що проведено на основі одночасткової моделі.